Faktor Penentu Keputusan Masyarakat Menjadi Pekerja Migran Indonesia - Zulfan Fikriansyah; Aan Julia (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Indramayu Regency is the largest district in West Java as a supplier of migrant workers. One of the villages contributing to migrant workers is Bongas Village, Bongas District, where Bongas Village holds the title of a Human Trafficking Village and a Supply Village for Indonesian Migrant Workers (PMI). There are many programs formulated by the Bongas Village Government and the Kusuma Bongas Foundation, such as opening open schools, business training, providing Life Skills, etc. As an effort to empower PMI and post-PMI, in fact, they were unable to persuade migrant workers from Bongas Village to continue migrating. The purpose of this study was to identify the driving factors and the attracting factors of the residents of Bongas Village, Bongas District, in becoming PMI. This study uses a quantitative descriptive method. The data used is primary data with 100 respondents consisting of 73 Full PMI respondents and 27 respondent's families. Secondary data from BNP2TKI Indramayu, Indramayu Manpower Office, Village Profile. The analysis in this study uses a Likert scale. Based on the results of the study, the factors driving the decisions of the people of Bongas Village in becoming migrant workers were the highest indicators of skills and expertise with an average score of 383 and the highest pull factor was the wage indicator with an average score of 398. Then the highest pull factor is the wage indicator with an average score of 398. of the two variables, namely push and pull variables, the highest average is a determinant of migration. Abstrak. Kabupaten Indramayu merupakan kabupaten terbesar di Jawa Barat sebagai penyalur pekerja migran. Salah satu Desa penyumbang pekerja migran adalah Desa Bongas Kecamatan Bongas dimana Desa Bongas menyandang predikat sebagai Desa penjual manusia dan Desa pemasok pekerja migran Indonesia (PMI). Ada banyak program yang di rumuskan oleh Pemerintah Desa Bongas dan Yayasan Kusuma Bongas seperti membuka sekolah terbuka, pelatihan usaha, memberikan pembekalan Life Skill dll. Sebagai upaya pemberdayaan PMI dan purna PMI nyatanya tidak bisa menyuturkan minat pekerja migran asal Desa Bongas untuk tetap bermigrasi. Tujuan penelitian ini adalah untuk mengidentifikasi faktor pendorong dan faktor penarik minat penduduk Desa Bongas Kecamatan Bongas dalam menjadi PMI. Penelitian ini menggunakan metode deskriptif kuantitatif. Data yang digunakan yaitu data primer dengan responden 100 orang terdiri dari 73 responden Purna PMI dan 27 responden keluarga. Data sekunder dari BNP2TKI Indramayu, DISNAKER Indramayu, Profil Desa. Analisis dalam penelitian ini menggunakan skala likert. Berdasarkan hasil penelitian bahwa faktor pendorong penentu keputusan masyarakat Desa Bongas dalam menjadi pekerja migran yang paling tinggi adalah indikator keterampilan dan keahlian dengan nilai rata-rata skor sebesar 383 dan faktor penarik yang paling tinggi adalah indikator upah dengan nilai rata-rata skor sebesar 398. Kemudian dari kedua variabel yaitu variabel pendorong dan penarik di rataratakan yang paling tinggi sebagai penentu migrasi.